2019
DOI: 10.1039/c9ta05245c
|View full text |Cite
|
Sign up to set email alerts
|

A carbon dot-catalyzed transesterification reaction for the production of biodiesel

Abstract: Biodiesel fuel production remains one of the most promising alternatives to non-renewable fossil fuels such as conventional oil and diesel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Polyaniline (PANI), as a p-type semiconductor, can generate photocurrent when exposed to light radiation and has significant photoelectric conversion characteristics, which makes it very hopeful as a candidate material for photoassisted electrocatalytic devices. Furthermore, PANI can provide protons in the reaction, promoting the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Carbon dots (CDs are monodisperse graphite dots of less than 10 nm in size) possess a unique photoelectric effect and high catalytic activity for various reactions. ,, Meanwhile, it has been reported that the electrode prepared by CDs and a semiconductor composite will show better P-EC hydrogen production performance. , In addition, the advantages of low cost, easy preparation, and abundant raw materials of PANI and CDs may make photoassisted electrocatalytic hydrogen production to be a promising industrial route. …”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline (PANI), as a p-type semiconductor, can generate photocurrent when exposed to light radiation and has significant photoelectric conversion characteristics, which makes it very hopeful as a candidate material for photoassisted electrocatalytic devices. Furthermore, PANI can provide protons in the reaction, promoting the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Carbon dots (CDs are monodisperse graphite dots of less than 10 nm in size) possess a unique photoelectric effect and high catalytic activity for various reactions. ,, Meanwhile, it has been reported that the electrode prepared by CDs and a semiconductor composite will show better P-EC hydrogen production performance. , In addition, the advantages of low cost, easy preparation, and abundant raw materials of PANI and CDs may make photoassisted electrocatalytic hydrogen production to be a promising industrial route. …”
Section: Introductionmentioning
confidence: 99%
“…The use of a magnetic recyclable PIC also simplifies the biodiesel production process and reduces the generation of waste pollutants, which overcomes the drawbacks of the most widely adopted alkaline catalyst (KOH) in industry. 34,35 However, merely adjusting the surface affinity of the magnetic PICs failed to make the static soybean oil/methanol emulsions remain stable for enough time at the reaction temperature. Under static conditions, the ex-field that causes emulsion destabilization must be gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the merits of high performance and easy recovery of magnetic PICs, recently, we constructed several magnetic PICs loaded with organic base 1,1,3,3-tetramethylguanidine (TMG) for catalyzing transesterification of soybean oil (triglyceride) with methanol, and realized a high biodiesel yield (98.6%) under low-speed stirring (300 rpm). The use of a magnetic recyclable PIC also simplifies the biodiesel production process and reduces the generation of waste pollutants, which overcomes the drawbacks of the most widely adopted alkaline catalyst (KOH) in industry. , However, merely adjusting the surface affinity of the magnetic PICs failed to make the static soybean oil/methanol emulsions remain stable for enough time at the reaction temperature. Under static conditions, the ex-field that causes emulsion destabilization must be gravity. , In aqueous–organic type emulsion, the gravity of PICs is normally ignored due to their small size, and the adsorption of PICs at water–oil interface is extremely stable owing to large interfacial tension .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon dots (CDs) have emerged as candidates for various applications due to their low cost and chemical toxicity, optical properties, and stability. The implementation of CDs for light-conversion applications as a new generation of photosensitizers has also increased as a result of their high photostability and tunable light absorption. , Moreover, these nanomaterials have shown photocatalytic activity for the degradation of organic contaminants, water splitting/hydrogen production, and redox catalysis of different organic reactions to produce high value-added chemicals by visible light. The latter has been relatively underexplored with greater focus on the degradation of organic dyes likely owing to the logistical simplicity regarding reaction monitoring and product isolation/characterization. , In a marriage of the two materials discussed ( vida supra ), we anticipate that the surface functionalization of ZnO NWs with CDs will open new avenues for the engineering and development of “green” nanohybrid devices. ,, To date, the design of such devices is partially hindered by fast electron–hole recombination kinetics, device stability, low quantum yields, and a general lack of understanding about the molecular processes occurring at the interface of such heterogeneous photoelectrodes …”
Section: Introductionmentioning
confidence: 99%